When the (hetero)norms shudder the daily life of children's education: conversations with teachers about the gender marks expressed in interactions among children - Paula Rios de Freitas; Dilton Ribeiro Couto Junior; Felipe da Silva Ponte de Carvalho (Universidade Federal de Santa Catarina, 2018)
As a result of a recently completed research, the aim of this work is to investigate, from the point of view of teachers of Children's Education, how gender marks are present in the interaction among children of a Rio de Janeiro public school. Given the need to destabilize the heterocentric regime that seeks, unceasingly, to normalize bodies, genders and sexualities, this research is anchored in a proposal that encourages other ways of looking/(re)thinking the world in favor of the need to create strategies to contest heteronormativity. In order to do this, debates held with teachers from this public school encouraged us to reflect on how the games played by children destabilize the regulatory norms of gender, since it favors the (re)creation of other (im)possible worlds.